Discussions on sensitive issues - Sutterby, John A., 1966- (Bingley, U.K. : Emerald, 2015)
It is important that early educators view sensitive topics not as problems, but as subjects that are part of our global society. Early educators need to engage children in conversations in which to consider and share diverse perspectives. Early educators also should examine their own experiences when addressing these serious issues. This volume contains chapters that invite conversations about sensitive issues to help educators, children and families use real-life experiences to construct knowledge about their world and other people.
Becoming color-conscious : preparation to address young children's curiosity about race / Kristen M. Kemple, Michelle G. Harris, Il Rang Lee -- Addressing race and racism in early childhood : challenges and opportunities / Flora Farago, Kay Sanders, Larissa Gaias -- The diversity teacher belief q-sort : a springboard for reflective conversations / Karin H. Spencer, Lorelei E. Pisha -- Ethnicity, self-regulation and academics in preschool / Ruth V. Guirguis -- Addressing classism in early childhood education : how social-class sensitive pedagogy and the Montessori method can work together / Olivia Christensen, Kelly Gast -- Maltreatment in early childhood and the roles of early childhood educators / Victor Villarreal, Maria J. Castro -- Is he a girl? Meeting the needs of children who are gender fluid / Robin K. Fox -- Trauma and young children : how the problem plays out / Jennifer Stone, Susan Bray.
Print version record
Keywords: Education -- General; Education; Early childhood education -- United States; Early childhood educators -- United States; Discrimination in education -- United States; Racism in education -- United States